Karakteristik Hidroksiapatit Porous dari Prekursor Cangkang Keong Sawah dan Bahan Porogen Pati Sukun - Endang Sulistyawati; Robertinus Filustra Siregar Siregar (Eksergi, 2019)
Hydroxyapatite [Ca10(PO)4(OH)2] is a biomaterial used in bone implants to repair damaged tissue bones. Hydroxyapatite has biocompatible and osteoconductive properties. Hydroxyapatite synthesis is carried out by reacting Ca and P with a mole ratio of 1,67. One source of calcium precursors is conch shell with a CaCO3 content of 48,02%. The addition of porogen breadfruit starch serves to form pores so that it can accelerate the process of nutrient infiltration in bone. The study began with the calcination of conch shells at 900oC for 4 hours, to obtain calcium oxide (CaO) compounds. Calcium and phosphate reactions were carried out at 60oC and the stirring time was 3 hours. The hydroxyapatite produced was sintered at 900oC for 4 hours and analyzed using FTIR, AAS, UV-VIS, SEM, XRD, and compressive strength. The analysis solid and porous hydroxyapatite showed a comparison of calcium and phosphorus respectively 1.677 and 1.673, so that hydroxyapatite was close to the hydroxyapatite standard. Hydroxyapatite dense has a particle size of 0.396 μm, while porous hydroxyapatite has a particle size of 0.9135 μm and a pore of 0.655 μm. Hydroxyapatite dense and porous compressive strength are 19.61 MPa and 9,807 MPa respectively, so porous hydroxyapatite is more effective in nutrient infiltration to repair bone damage.